Cold for gravity, heat for microgravity: A critical analysis of the “Baby Astronaut” concept - Meigal, Alexander; Gerasimova-Meigal, Liudmila (Frontiers in Space Technologies, 2022)
Existing literature suggests that temperature and gravity may have much in common as regulators of physiological functions. Cold, according to existing literature, shares with gravity common effects on the neuromuscular system, while heat produces effect similar to those of microgravity. In addition, there are studies evidencing unidirectional modification of the motor system to heat and hypoxia. Such agonistic relationship in a triad of "microgravity, heat and hypoxia", and in a pair "cold and gravity" in their effect on the neuromuscular system may have evolutionary origins. To address this problem, ten years ago we came up with a concept with working name Baby Astronaut hypothesis, which posed that "Synergetic adaptation of the motor system to different environments come from their ontogenetic synchronicity”. More specifically, the synchronicity of microgravity (actually, the “wet immersion” model of microgravity), higher temperature, and hypoxia are the characteristic of the intrauterine environment of the fetus. After childbirth, this group of factors is rapidly replaced by the "extrauterine", routine environment characterized by Earth gravity (1 G), normoxia, and lower ambient temperature. Physiological effect of cold and gravity on the motor system may well be additive (synergistic). We earlier estimated a "gravity-substitution" potential of cold-induced activity and adaptation to cold as 15-20% of G, which needs further validation and correction. In this study, we sought to critically analyze the interaction of temperature and gravity, based on the concept of Baby Astronaut, using data from new academic literature. We have come to the conclusion that the concept of Baby Astronaut can be regarded as valid only for species such as a rat (immature, altricial species), but not for a human fetus. Several confirmatory experiments were suggested to verify (or falsify) the concept, which would allow to consider it as empirical. In addition, the interaction of temperature and gravity may be of practical interest in the fields of neurorehabilitation and habilitation in childhood for constructing a physical environment, which would help strengthen or weaken muscle tone in specific muscles.